2017
DOI: 10.1080/13816810.2017.1363245
|View full text |Cite
|
Sign up to set email alerts
|

Nance–Horan syndrome in females due to a balanced X;1 translocation that disrupts the NHS gene: Familial case report and review of the literature

Abstract: The Nance-Horan syndrome is an X-linked disorder characterized by congenital cataract, facial features, microcornea, microphthalmia, and dental anomalies; most of the cases are due to NHS gene mutations on Xp22.13. Heterozygous carrier females generally present less severe features, and up to 30% of the affected males have intellectual disability. We describe two patients, mother and daughter, manifesting Nance-Horan syndrome. The cytogenetic and molecular analyses demonstrated a 46,X,t(X;1)(p22.13;q22) karyot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Previous studies illustrated that variations in the NHS gene could induce X-linked cataracts and NHS [1012]. However, the identical association between the genotype and phenotype was unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies illustrated that variations in the NHS gene could induce X-linked cataracts and NHS [1012]. However, the identical association between the genotype and phenotype was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The mother had a preferential inactivation of the normal X chromosome and no mRNA isoform of NHS was detected. This study implied that NHS could be due to the disruption of NHS gene expression [12].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed an additional report of NHS disruption due to a translocation. In this case, disruption was caused by a balanced (X;1) translocation [ 21 ]. As with our report, the patients examined in this study were female.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a preferential inactivation of the normal X chromosome has been reported to cause X-linked disorders in the female carriers of an X-autosome translocation carriers [ 23 25 ]. It appears to occur in individuals with a balanced X-autosome translocation disrupting the NHS gene, and cause a phenotype consistent with NHS, in particular the facial characteristics and cataracts [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation